2017
DOI: 10.4172/2329-9126.1000323
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Value in the Early Diagnosis and Exclusion of Idiopathic Hypertrophic Pyloric Stenosis: 10 Years Experience at Babylon Governorate

Abstract: Background: Idiopathic Hypertrophic Pyloric Stenosis (IHPS) is one of the most common surgical conditions of early infancy, presenting in 1.5 to 4 per 1000 live births. Despite this high prevalence, the precise etiology remains poorly understood. The diagnosis is made primarily with history and physical examination. Projectile, non-bilious vomiting is the classic presentation of an infant with IHPS. The typical physical exam findings include visible peristaltic waves and palpation of the olive mass in the uppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…19 Among all positive cases, 75.36% were male and 34.64% were female with a male to female ratio of almost 3:1. 19 It was concluded that sonography was a noninvasive and harmless imaging modality for the diagnosis of IHPS. 19 In a study by Hernanz-Schulman, 22 the etiological hypotheses and epidemiology of the condition was examined and the evidence supporting the various diagnostic investigations conducted.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…19 Among all positive cases, 75.36% were male and 34.64% were female with a male to female ratio of almost 3:1. 19 It was concluded that sonography was a noninvasive and harmless imaging modality for the diagnosis of IHPS. 19 In a study by Hernanz-Schulman, 22 the etiological hypotheses and epidemiology of the condition was examined and the evidence supporting the various diagnostic investigations conducted.…”
Section: Discussionmentioning
confidence: 96%
“…17,18 Sometimes it can progress to almost near-complete occlusion of the gastric outlet, leading to projectile vomiting. 19,20 IHPS occurs in approximately 0.2 to 0.35 of live births, although rates and trends vary markedly from region to region. 21 It is more common in males than in females.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations